2021
DOI: 10.1093/bbb/zbaa039
|View full text |Cite
|
Sign up to set email alerts
|

Role of gambogenic acid in regulating PI3K/Akt/NF-kβ signaling pathways in rat model of acute hepatotoxicity

Abstract: The purpose of this study is to investigate the protective effect of gambogenic acid (GA) in acetaminophen (APAP)-induced hepatotoxicity in rat models. GA (10 mg/kg) was administered intraperitoneal (i.p.) to rats for 7 consecutive days followed by APAP (500 mg/kg) single dose (i.p.) on the final day after GA administration. The levels of MDA, GSH, SOD, CAT, GPx, GST, ALP, AST, ALT, proinflammatory cytokines (TNF-α, IL-1β, IL-6), apoptosis markers (caspase-3 and -9, Bax, Bcl-2), 4-hydroxynonenal (4-HNE), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…APAP-induced cell death is caused by massive mitochondrial dysfunction and damage to the nuclear DNA [ 55 ]. The PI3K/Akt signaling pathway is a crucial point for hepatoprotection via inhibiting apoptosis under oxidative stress and inflammatory conditions [ 24 ]. PI3K is an intracellular phosphatidylinositol kinase, and Akt is one of its key downstream effectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…APAP-induced cell death is caused by massive mitochondrial dysfunction and damage to the nuclear DNA [ 55 ]. The PI3K/Akt signaling pathway is a crucial point for hepatoprotection via inhibiting apoptosis under oxidative stress and inflammatory conditions [ 24 ]. PI3K is an intracellular phosphatidylinositol kinase, and Akt is one of its key downstream effectors.…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the Bcl-2 family, Bax can interact with and inactivate Bcl-2 to enhance apoptosis [ 23 ]. Ding et al showed that the natural active ingredient gambogenic acid can exhibit antiapoptotic activity by activating the signaling pathway of PI3K/Akt [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of its associated downstream molecules, that is, c-Myc and p-Akt, has been observed. Furthermore, gambogenic acid exerts anti-inflammatory and antiapoptotic effects against in vivo acute hepatotoxicity by regulating the PI3K/Akt and NF-κB signaling pathways [125]. Its inhibitory effect on NF-κB signaling has also been found to suppress growth and metastasis of bladder cancer cells [126].…”
Section: Gambogenic Acidmentioning
confidence: 99%
“…Therefore, it is necessary to study this pair of isomers separately. GNA, differing from GA in having an open pyran ring, exhibits anticancer activity in colorectal cancer (Zhao et al, 2020), hepatocellular carcinoma (Yu, Zhao, Wang, et al, 2016), glioblastoma (Chen et al, 2012) and lung adenocarcinoma (Huang et al, 2019; Xu et al, 2018), besides cytotoxicity and anti‐inflammatory activity (Ding et al, 2021; Tao et al, 2009; Yu, Zhao, Zhang, et al, 2016). Related studies have proved that β ‐MA and IGNA also possess potential anticancer and antibacterial effects (Li et al, 2015; Reutrakul et al, 2007; Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%